2020
DOI: 10.2967/jnumed.119.238279
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging Modalities: Principles and Applications in Preclinical Research and Clinical Settings

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to (1) compare and judge the most appropriate imaging technique based on disease nature; (2) apply excitation source and appropriate readout depending on imaging techniques; and (3) recognize and interpret published molecular imaging data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 92 publications
(95 reference statements)
0
50
0
3
Order By: Relevance
“…Fluorescence-guided imaging using molecularly targeted agents to delineate tumors for diagnosis and to guide surgical resection has started to enter the clinical research space in recent years (30). These include studies on ovarian, colorectal and breast cancer (31). While only late stage clinical studies will be able to prove the added clinical value in terms of survival benefit of these newer modalities compared to standard diagnosis and surgical resection, early phase clinical studies are crucial to show feasibility of lesion detection, dose-finding, and provide exploratory data on sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence-guided imaging using molecularly targeted agents to delineate tumors for diagnosis and to guide surgical resection has started to enter the clinical research space in recent years (30). These include studies on ovarian, colorectal and breast cancer (31). While only late stage clinical studies will be able to prove the added clinical value in terms of survival benefit of these newer modalities compared to standard diagnosis and surgical resection, early phase clinical studies are crucial to show feasibility of lesion detection, dose-finding, and provide exploratory data on sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…reduced nicotinamide adenine dinucleotide (NADH), hemoglobin or collagen), or reporter genes (e.g. Green Fluorescent Protein) [152,153]. This technology includes modalities such as Fluorescence Imaging, Bioluminescent Imaging, Optical Coherence Tomography (OCT), Photoacoustic Imaging, Diffuse Optical Tomography (DOT), Super-resolution Microscopy and Terahertz Tomography [152,154,155].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Optical imaging has the potential to be noninvasive, nontoxic and cost-effective to quantify vascularization, permeability, hemoglobin, oxygen saturation (StO2) and concentration in breast tumors. Studies have shown that vascularization and StO2 of breast tumors are related to hypoxia, which is highly associated with malignant tumors due to their size [151,153].…”
Section: Optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…MI is used to study conditions that underlie normal physiology and pathologies. MI modalities include, but are not limited to, fluorescence imaging, bioluminescence imaging, near-infrared imaging (NIR), single photon emission computed tomography (SPECT), positron emission tomography (PET), and magnetic resonance imaging [12][13][14][15]. While the sensitivity of these modalities varies, they can provide information of high spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%